2005
DOI: 10.1111/j.1538-7836.2005.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 haplotype modulates platelet response to aspirin

Abstract: Summary.  Background: Aspirin (acetylsalicylic acid) irreversibly inhibits platelet cyclooxygenase (COX)‐1, the enzyme that converts arachidonic acid (AA) to the potent platelet agonist thromboxane (TX) A2. Despite clear benefit from aspirin in patients with cardiovascular disease (CAD), evidence of heterogeneity in the way individuals respond has given rise to the concept of ‘aspirin resistance.’Aims: To evaluate the hypothesis that incomplete suppression of platelet COX as a consequence of variation in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
3
10

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(133 citation statements)
references
References 15 publications
2
118
3
10
Order By: Relevance
“…Similarly, Colaizzo et al 19) revealed an association between the COX-2 G765C polymorphism and cerebrovascular ischemia, suggesting that the COX-2 gene is a susceptibility locus for the risk of cerebrovascular ischemic disease; however, Cipollone et al 20) found that the COX-2 G765C polymorphism could reduce urine 11-dehydro-thromboxane B2 (11-dTxB2) and was a protective factor against myocardial infarction and ischemic stroke. In addition, Frelinger et al 21) and Meen et al 22) have shown that AR in a number of subjects may be independent of both COX-1 and COX-2; however, Maree et al 23) showed that genetic variability in COX-1 appears to modulate both arachidonic acid (AA)-induced platelet aggregation and thromboxane generation. Heterogeneity in the way patients respond to aspirin may in part reflect COX-1 genotype variations.…”
Section: Study Populationsmentioning
confidence: 99%
“…Similarly, Colaizzo et al 19) revealed an association between the COX-2 G765C polymorphism and cerebrovascular ischemia, suggesting that the COX-2 gene is a susceptibility locus for the risk of cerebrovascular ischemic disease; however, Cipollone et al 20) found that the COX-2 G765C polymorphism could reduce urine 11-dehydro-thromboxane B2 (11-dTxB2) and was a protective factor against myocardial infarction and ischemic stroke. In addition, Frelinger et al 21) and Meen et al 22) have shown that AR in a number of subjects may be independent of both COX-1 and COX-2; however, Maree et al 23) showed that genetic variability in COX-1 appears to modulate both arachidonic acid (AA)-induced platelet aggregation and thromboxane generation. Heterogeneity in the way patients respond to aspirin may in part reflect COX-1 genotype variations.…”
Section: Study Populationsmentioning
confidence: 99%
“…ADP receptor P2Y12 (P2RY12 G52T) 4 ; 12. Prostaglandin G/H synthase 1 (cyclooxygenase-1) (PTGS1 C50T) 43 ; and 13. TXA2 receptor (TBXA2R C795T or C924T or G1686A).…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
“…sequence variation in CoX-1 as it relates to aspirin response has been investigated, with studies yielding inconsistent data. 15,16 similar studies have been concluded with respect to snps that reside within the glycoprotein iiia gene. these too have led to contradictory findings.…”
Section: Pharmacogenomics Of Aspirinmentioning
confidence: 72%